2003
DOI: 10.1093/emboj/cdg269
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of tRNA(m1G37)methyltransferase: insights into tRNA recognition

Abstract: contributed equally to this work tRNA(m 1 G37)methyltransferase (TrmD) catalyzes the transfer of a methyl group from S-adenosyl-Lmethionine (AdoMet) to G 37 within a subset of bacterial tRNA species, which have a G residue at the 36th position. The modi®ed guanosine is adjacent to and 3¢ of the anticodon and is essential for the maintenance of the correct reading frame during translation. Here we report four crystal structures of TrmD from Haemophilus in¯uenzae, as binary complexes with either AdoMet or S-aden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
207
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(223 citation statements)
references
References 43 publications
15
207
1
Order By: Relevance
“…The TrmD structure was solved at 2.25 Å resolution with the Haemophilus influenzae enzyme, which shares 83% sequence identity and 91% similarity with E. coli TrmD. As seen in the previous structures of TrmD (Ahn et al 2003;Elkins et al 2003), the two active sites in the dimeric H. influenzae enzyme were symmetrically assembled in the dimer interface, with each consisting of residues from the AdoMet-binding motifs in the N-terminal domain of one monomer and residues from the tRNAbinding motifs in the C-terminal domain of the second monomer. A comparison with the previous AdoMet-bound structure of TrmD (Ahn et al 2003) revealed that the two adenosine molecules bound in the new structure were in virtually overlapping positions as the adenosine moiety of the previous structure (Fig.…”
Section: X-ray Structural Analysis Of Adenosine-bound Trmd and Trm5 Cmentioning
confidence: 90%
See 2 more Smart Citations
“…The TrmD structure was solved at 2.25 Å resolution with the Haemophilus influenzae enzyme, which shares 83% sequence identity and 91% similarity with E. coli TrmD. As seen in the previous structures of TrmD (Ahn et al 2003;Elkins et al 2003), the two active sites in the dimeric H. influenzae enzyme were symmetrically assembled in the dimer interface, with each consisting of residues from the AdoMet-binding motifs in the N-terminal domain of one monomer and residues from the tRNAbinding motifs in the C-terminal domain of the second monomer. A comparison with the previous AdoMet-bound structure of TrmD (Ahn et al 2003) revealed that the two adenosine molecules bound in the new structure were in virtually overlapping positions as the adenosine moiety of the previous structure (Fig.…”
Section: X-ray Structural Analysis Of Adenosine-bound Trmd and Trm5 Cmentioning
confidence: 90%
“…While different in spatial configuration, each network is elaborate and comprehensive in the stabilization of the N 1 , N 6 , and N 7 of the adenine ring, the 29-and 39-OH of the ribose, and the carboxyl and amino groups of methionine in the methyl donor. These stabilizing forces are well visualized in a binary structure of TrmD with AdoMet and are preserved in a product complex with S-adenosyl homocysteine (AdoHcy) (Ahn et al 2003;Elkins et al 2003). They are also clearly identified in a binary structure of Trm5 with sinefungin and in a ternary structure with AdoMet and tRNA (Goto-Ito et al 2008).…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Eukaryotes and archaea employ the Trm5 enzyme (Bjork et al 2001;Christian et al 2004), whereas bacteria use the TrmD enzyme (Bystrom and Bjork 1982a,b). While both enzymes use AdoMet as the methyl donor to convert G37-tRNA to m 1 G37-tRNA, they are fundamentally distinct in structure (Ahn et al 2003;Christian et al 2004;Goto-Ito et al 2008, 2009, in kinetics (Christian et al 2010b), and in substrate recognition (Christian and Hou 2007;Lahoud et al 2011;Sakaguchi et al 2012). The lack of similarity between TrmD and Trm5 has led to the suggestion that specific targeting of TrmD, without affecting the Homo sapiens Trm5 (HsTrm5), would be a highly attractive strategy in developing the next generation of antibiotics (White and Kell 2004).…”
Section: Introductionmentioning
confidence: 99%
“…2), it appears that the RNA-modifying enzymes responsible for producing the 5-taurinomethyl and 2-thio groups of the wobble bases of these mt tRNAs belong to a class of enzymes that recognize the whole tertiary structure of the tRNA, 15 such as tRNA m 1 G37 methyltransferase (TrmD). 16 In other words, the positions of these pathogenic point mutations act as determinants for the biosynthesis of τm 5 U and τm 5 s 2 U. We have recently reported the identification and characterization of the tRNA-modifying enzyme MTU1 (mitochondrial tRNA-specific 2-thiouridylase 1) that is responsible for the 2-thiolation of the wobble position in human and yeast mt tRNAs.…”
Section: Post-transcriptional Wobble Modification Deficiency In Mutanmentioning
confidence: 99%